Simulation of Data De-noising System using Improved PSO Software Algorithm (American Journal of Engineering , Mechanics and Architecture (2993-2637), 2025)
In an RF environment, noise that starts with a few references ruins the display of telecommunications systems. Non-linearity at the RF section, time-varying warm noise inside the collector radio framework, with noise through neighboring organization hubs can all contribute to the noise at the receiver of a broadband framework, such as intellectual radios. For intelligent radios, a few denoising techniques have been developed; some are used for range detection, while others are used to obtain loud signals during conversation. Less mean square (LMS) and its variants are illustrations of part of such strategies employed to eliminate noise in detected waveforms. In any case, these computations perform poorly when dealing with non-straight signals and are unable to provide a globally optimal solution for noise retraction. In this way, the use of global inquiry advancement techniques, such as developmental calculations, is taken into account for noise retraction. In this study, LMS computations are performed and their displays evaluated, together with an upgraded particles swarm optimization improved (PSO). The supplied waveform was subjected to broad recreations in which non-straight irregular noise and Gaussian noise were included. Two metrics were used to complete the presentation examination: mean square error and bit error rate. The results demonstrate that for both Gaussian and nonlinear arbitrary noise, the enhanced PSO outperforms LMS.